198 Endoscope-Assisted Suturectomy for Metopic Synostosis: 15-year Experience at Boston Children's Hospital. (April 2023) - Hori, Yusuke; Albanese, John; Staffa, Steven; Piwowarczyk, Paulina; Northam, Weston; Proctor, Mark R.
Abstract : INTRODUCTION: Metopic synostosis is a subtype of craniosynostosis characterized by trigonocephaly. Endoscope-assisted suturectomy has shown its relevance as an alternative option with a lower rate of transfusion, short hospital length of stay (LOS) while maintaining comparable cosmetic outcome when compared with open repair. However, no previous reports have shown the long-term results of this procedure and factors associated with outcome. METHODS: 133 pediatric patients with metopic synostosis treated with endoscope-assisted suturectomy between 2006 and 2021were retrospectively reviewed. Peri- and post-operative variables were extensively collected. LOS and the length of helmet therapy were defined as primary outcome. Logistic regression or median regression analysis was conducted for multivariable analysis to identify factors associated with longer LOS and length of helmet therapy. P<0.05 was defined as statistically significant. RESULTS: Median age was 93-days, median weight was 5.8 kg and median cranial index 0.82. Eighty-two percent of patients were male. Median surgical time was 48 minutes and estimated blood loss was 40 mL. 10 patients (7.5%) received intra- or post-op transfusion. Median pre-op Hb level was 10.1 g/dL with immediate postop level of 7.4 g/dL. Median hospital LOS was 1 day. The median length of helmet therapy was 6 months. Only one patient required minor correctional surgery for recurrence in long-term. In multivariable analysis, larger number of the pain medications administered within 24 hours after the operation (OR 1.79; P<0.001) and lower weight (OR 2.33 per kg lower; P=0.024) were significantly associated with longer LOS. Larger pre-op cranial index (OR 11.8; P=0.022) was significantly associated with longer length of helmet therapy. CONCLUSIONS: Our comprehensive study demonstrates that endoscope-assisted suturectomy is a safe and effective treatment for metopic synostosis and novel predictive factors associated with outcomes.